Safety, accuracy, and prediction of prognosis in patients with end-stage chronic kidney disease undergoing dobutamine stress cardiac magnetic resonance imaging - Weberling, Lukas D.; Seitz, Sebastian; Salatzki, Janek; Ochs, Andreas; Haney, Ailís C.; Siry, Deborah; Heins, Jannick; Steen, Henning; Frey, Norbert; André, Florian (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Advanced chronic kidney disease (CKD) is an independent risk factor for coronary artery disease (CAD). Due to its unique uremia-derived pathophysiology of atherosclerosis and the limitations of using potentially harmful contrast agents the best non-invasive approach to assess CAD in these patients remains unclear. We sought to investigate the accuracy, safety, and prognosis of patients with severe CKD undergoing dobutamine stress cardiac magnetic resonance imaging (CMR).Materials and Methods: In this retrospective, single-center study patients on dialysis or with a glomerular filtration rate <15ml/min/1,73m 2 who underwent dobutamine stress CMR were included. Rest and stress wall motion analysis was performed using dobutamine/ atropine as stressor. Target heart rate was 85% of maximum heart rate. Periprocedural adverse events and 1-year follow-up data were obtained.Results: 176 patients (127 men, 49 women) with a mean age of 60.9±14.7years were included. 156 were on permanent dialysis. Short-term symptoms such as angina or shortness of breath during stress-CMR were frequent (22.1%), but major complications were rare (1 myocardial infarction, 0.6%). The 1-year event rate was high (16.4%) with significant independent correlation to reduced ejection fraction at rest (p=0.037) and failure to achieve target heart rate (p=0.029). Overall accuracy for predicting significant CAD was good (sensitivity 71.4%, specificity 98.4%) and excellent if target heart rate was achieved (83.3%, 97.9%). A negative stress CMR was highly predictive for the absence of MACE or any coronary revascularization during one-year follow-up (negative predictive value 95.0%).Discussion: Dobutamine stress CMR is a safe and accurate diagnostic imaging technique in patients at advanced stages of chronic kidney disease. A reduced ejection fraction and the inability to reach target heart rate are independent predictors of poor outcome.